(untitled) (Indonesian Minority Justice Review, 2024)
This paper explores the intersectionality of gender and minority rights in Indonesia, focusing on how laws and policies affect women from minority groups. Indonesia’s legal system, while offering some protections for gender equality through the 2004 Law on the Elimination of Domestic Violence and the 2007 Law on Gender Equality, often fails to account for the compounded discrimination faced by women from ethnic, religious, or sexual minorities. The study examines the legal challenges encountered by women belonging to these marginalized groups, including issues of access to justice, protection from violence, and participation in public life. Using case studies of women from indigenous communities, religious minorities, and the LGBTQ+ population, the paper highlights how these women often face both gender-based and minority-based discrimination within Indonesia’s legal and social systems. The research reveals that while gender rights laws have been instrumental in advancing the status of women in some areas, the legal system’s failure to address intersectional forms of discrimination leaves minority women particularly vulnerable. The paper concludes by advocating for more inclusive legal reforms that recognize the unique challenges faced by women at the intersection of gender and minority status, urging for targeted policies that promote both gender equality and minority rights.